Austria's Competitiveness in Trade in Services - Julia Woerz (FIW - Research Centre International Economics, 2008)
Trade in services is a rapidly growing phenomenon. Consequently, the question of individual countries? competitiveness in trade in services is of increasing importance. In this paper we describe patterns of competitiveness in services sectors for EU members over the period 1995 to 2005, differentiating between 11 individual service activities. We find a clear East-West divide in general and especially for Austria's strengths and weaknesses in the services sector. Austria's competitiveness lies in traditional, yet globally declining sectors such as transport and travel and is weak in industries such as insurance, computer and information, communication services and royalties and licence fees. The latter two industries are characterized by above-average levels of competitiveness within the EU. We then investigate the influence of factors such as labour productivity, unit labour costs, industry size and skill endowments for services sector competitiveness in the EU member states.
Keywords: F14; 330; export of services; trade in services; comparative advantage; competitiveness